Dextran Sulfate Sodium Salt-Induced Colitis Aggravates Gut Microbiota Dysbiosis and Liver Injury in Mice With Non-alcoholic Steatohepatitis - Shen, Bo; Wang, Junjun; Guo, Yuecheng; Gu, Tianyi; Shen, Zhenyang; Zhou, Cui; Li, Binghang; Xu, Xianjun; Li, Fei; Zhang, Qidi; Cai, Xiaobo; Dong, Hui; et al. (Frontiers in Microbiology, 2021)
Objective: Inflammatory bowel disease (IBD) is characterized by gut microbiota dysbiosis, which is also frequently observed in patients with nonalcoholic fatty liver disease. Whether gut microbiota dysbiosis in IBD patients promotes the development of nonalcoholic steatohepatitis (NASH) remains unclear. We aimed to explore the role of gut microbiota dysbiosis in the development of NASH in mice with dextran sulfate sodium salt (DSS) induced colitis Design: DSS was used to induce colitis, and a high-fat (HF) diet in combination with a high-fructose diet was used to induce NASH in mice. Mice were treated with 1% DSS in cycles, and each cycle consisted of 7 days of DSS administration followed by a 10-day interval. The cycles were repeated throughout the experimental period of 19 weeks. Pathological alterations in colitis and NASH were validated by hematoxylin and eosin, oil red O, Sirius red staining, and immunofluorescence. Gut microbiota was examined by 16S rRNA sequencing, and gene expression profiles of hepatic non-parenchymal cells (NPCs) were detected by RNA sequencing. Results: DSS administration enhanced the disruption of the gut-vascular barrier and aggravated hepatic inflammation and fibrosis in mice with NASH. DSS-induced colitis was accompanied by gut microbiota dysbiosis, characterized by alteration of the core microbiota composition. Specifically, gut microbiota dysbiosis was characterized by enrichment of lipopolysaccharide producing bacteria and decreased abundance of short-chain fatty acid producing bacteria. Gene expression analysis of liver NPCs indicated that compared to the HF group, genes related to both inflammatory response and angiocrine signaling were altered in the DSS+HF group. The expression levels of inflammation-related and vascular development genes correlated significantly with the abundance of p_Proteobacteria, g_Bacteroides, or f_S24-7 in the gut microbiota, implying that gut microbiota dysbiosis induced by DSS might aggravate hepatic inflammation and fibrosis by altering the gene expression in NPCs. Conclusions: DSS-induced colitis may promote the progression of liver inflammation and fibrosis by inducing microbiota dysbiosis, which triggers an inflammatory response and disrupts angiocrine signaling in liver NPCs. The abundance of gut microbiota was associated with expression levels of inflammation-related genes in liver NPCs, and may serve as a potential marker for the progression of NASH.